A linear-based trunk reservation routing algorithm for ATM networks - Atlasis, Antonios F.; Baltatzis, Evangelos D.; Stassinopoulos, George I.; Venieris, Iakovos S. (International journal of communication systems, 1999)
In this paper a practical routing algorithm is proposed that increases the network throughput irrespective of the network traffic load. Its effectiveness is based on an efficient cost function which achieves a successful trade‐off between the use of the minimum‐hop routes and the application of the load‐balancing concept. Moreover, it employs the known Trunk Reservation notion according to a probability that increases linearly with the traffic load. This results in an effective compromise of the performance of the algorithm between light and heavy traffic loads. Finally, its simplicity and its suitability for a real‐time application render it as an efficient routing algorithm for ATM networks. Copyright © 1999 John Wiley & Sons, Ltd.